Clinical delineation and natural history of the PIK3CA‐related overgrowth spectrum. Issue 7 (29th April 2014) - Keppler‐Noreuil, Kim M.; Sapp, Julie C.; Lindhurst, Marjorie J.; Parker, Victoria E.R.; Blumhorst, Cathy; Darling, Thomas; Tosi, Laura L.; Huson, Susan M.; Whitehouse, Richard W.; Jakkula, Eveliina; Grant, Ian; Balasubramanian, Meena; et al.
<x xml:space="preserve">Abstract</x> Somatic mutations in the phosphatidylinositol/AKT/mTOR pathway cause segmental overgrowth disorders. Diagnostic descriptors associated with PIK3CA mutations include fibroadipose overgrowth (FAO), Hemihyperplasia multiple Lipomatosis (HHML), Congenital Lipomatous Overgrowth, Vascular malformations, Epidermal nevi, Scoliosis/skeletal and spinal (CLOVES) syndrome, macrodactyly, and the megalencephaly syndrome, Megalencephaly‐Capillary malformation (MCAP) syndrome. We set out to refine the understanding of the clinical spectrum and natural history of these phenotypes, and now describe 35 patients with segmental overgrowth and somatic PIK3CA mutations. The phenotypic data show that these previously described disease entities have considerable overlap, and represent a spectrum. While this spectrum overlaps with Proteus syndrome (sporadic, mosaic, and progressive) it can be distinguished by the absence of cerebriform connective tissue nevi and a distinct natural history. Vascular malformations were found in 15/35 (43%) and epidermal nevi in 4/35 (11%) patients, lower than in Proteus syndrome. Unlike Proteus syndrome, 31/35 (89%) patients with PIK3CA mutations had congenital overgrowth, and in 35/35 patients this was asymmetric and disproportionate. Overgrowth was mild with little postnatal progression in most, while in others it was severe and progressive requiring multiple surgeries. Novel findings include: adipose dysregulation present in all patients, unilateral overgrowth that is predominantly left‐sided, overgrowth that affects the lower extremities more than the upper extremities and progresses in a distal to proximal pattern, and in the most severely affected patients is associated with marked paucity of adipose tissue in unaffected areas. While the current data are consistent with some genotype–phenotype correlation, this cannot yet be confirmed. © 2014 Wiley Periodicals, Inc.